Innovations in qualifying exams: toward student-centered doctoral training - Davidson, Adina O.; McLaughlin, Jacqueline E.; Layton, Rebekah L.; Brandt, Patrick D.; Jarstfer, Michael B. (Frontiers in Education, 2024)
The career paths of PhD scientists often deviate from their doctoral theses. As a result, the need to integrate student-centered career and professional development training is important to meet the needs of doctoral students. Qualifying exams (QEs) represent a significant milestone in progression toward graduation within most PhD Programs in the United States. These exams are commonly administered 2–3 years into a PhD program following the completion of coursework, with the primary objective of evaluating whether the candidate possesses the necessary knowledge and skills to progress with their dissertation research. To enhance the value of QEs and intentionally align them with the diverse career trajectories of our students, we explored the inclusion of student-centered assessments in a track with a Pharmaceutical Sciences PhD program. In this PhD program, one component of QEs is a series of monthly, written cumulative exams focused on recent scientific literature in the faculty and students’ discipline. To create a student-centered QE, the student and a faculty member collaborated to develop personalized assessments focused on career exploration and in alignment with individual student’s career goals. All students enrolled in the PhD track (n = 8) were invited to participate in a survey about their experience with the redesigned QE. A combination of Likert scale and short answer questions were collected; quantitative items were analyzed with descriptive statistics and qualitative items with thematic coding. A subset of survey participants (n = 5) participated in a focus group regarding their experience with both the Traditional Model QE and the redesigned Pilot Model QE. Two faculty interviews were conducted regarding the design, content, procedures, and evaluation of student QEs. The study design and analysis were grounded in the cognitive apprenticeship framework, with a focus on how the QEs were situated within the four domains of this framework: content, methods, sequencing, and sociology. Results revealed that this student-centered QE approach was perceived to be more aligned with student career aspirations and to have a high interest level and value for students without placing a substantial additional burden on participants. This suggests that it is a feasible mechanism for integrating student-centered assessment into QEs.